Sex Differences in the Response to Different Tinnitus Treatment - Van der Wal, Annemarie; Luyten, Tine; Cardon, Emilie; Jacquemin, Laure; Vanderveken, Olivier M.; Topsakal, Vedat; Van de Heyning, Paul; De Hertogh, Willem; Van Looveren, Nancy; Van Rompaey, Vincent; Michiels, Sarah; Gilles, Annick (Frontiers in Neuroscience, 2020)
Introduction: Tinnitus is a complex symptom requiring a thorough multidisciplinary assessment to construct an individual’s tinnitus profile. The Antwerp University Hospital hosts a tertiary tinnitus clinic providing intensive, multidisciplinary tinnitus care in the form of combinational psychological treatment with either Tinnitus Retraining Therapy (TRT)/Cognitive Behaviour Therapy (CBT) or TRT/Eye Movement Desensitisation and Reprocessing therapy (EMDR), high-definition transcranial direct current stimulation (HDtDCS), and physical therapy treatment (in cases of somatic influence of the neck or the temporomandibular area). Several factors may contribute to therapy effect of which the role of gender has recently gained more interest. As such, the current manuscript explores gender differences in the outcome of different tinnitus treatments. Methods: Data on treatment outcome of four distinct tinnitus treatments (1. HDtDCS; 2. Orofacial physical therapy; 3. Combination TRT + CBT and 4. Combination TRT + EMDR) were pooled and compared. Treatment outcome was assessed via the Tinnitus Functional Index (TFI). Participants completed the TFI at baseline, immediately after treatment and after 9 weeks (± 3 weeks) follow-up. To explore the effect of gender on different treatment outcomes, a linear mixed model was designed including Time point, Gender and Therapy Group as fixed factors as well as all interactions between these factors. Results: TFI scores improved significantly over time regardless of therapy group (p < 0.0001). A mean TFI decrease of at least 13 points was obtained by all participants except by those in the HD-tDCS. Significant interactions between Gender and Time point were identified in all groups except for the TRT +EMDR group. Female subjects improved more extensively than males in the HD-tDCS (p = 0.0009) and orofacial therapy group (p = 0.0299). Contrarily, in the TRT +CBT group, male participants showed a significant improvement whereas the mean TFI scores of female subjects remained on baseline levels (p = 0.0138). Conclusion: Our data suggest that male and female tinnitus patients seem to react differently to different therapy options. We strongly encourage further prospective studies to discern the relevance of gender in future guidance towards therapy.